Pembelajaran Kursus Bahasa Arab pada Era Pandemi Covid-19 - Adi Supardi (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2021)
Abstract This study aims to identify planning, strategies, problems and solutions for learning Arabic courses in the Covid-19 pandemic era at the Language Center of UIN Sunan Gunung Djati Bandung. This study uses a qualitative descriptive method in the form of a case study. Learning planning with online-based curriculum adaptation, such as the use of Whatsapp, Zoom and Youtube, giving structured assignments online, periodic orientation activities, and evaluations. Learning strategies use social media for students to do assignments, upload assignment videos to youtube, contact via whatsapp media by asking learning assignments given by the instructor, and provide educational games. Learning problems such as limited internet network, difficulty in objectivity of emotional and psychological assessments, difficulty sharing time with students, lack of motivation to learn, and scores that are still below the standard set by the instructor. The solution includes 2 main aspects, namely media technical and learning motivation. Media technicians should prepare adequate internet, monitor and supervise the use of media by the IT team, and develop more detailed standard operating procedures related to the use of learning media and media feasibility trials. Learning motivation should be in the form of more varied assignments using social media favored by students, uploading assignment content to Youtube, and providing special assistance for students who do not need assistance. Keywords: Learning Arabic courses; Covid-19 pandemic.